Motor abilities: methods of strength and strength endurance development in middle-school-aged boys in a 4-week physical training cycle - Veremeenko, V.Yu.; Khudolii, O.M.; Ivashchenko, O.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2019)
The study purpose was to develop a technology of programming for strength and strength endurance development in middle-school-aged boys in a 4-week physical training cycle. Materials and methods. The study participants were boys of 6th grade (n=35), 7th grade (n=36), 8th grade (n=36). The study materials were processed by the IBM SPSS 23 statistical analysis software. The following parameters were calculated: arithmetic mean (X); standard deviation (s). The probability of difference in statistical indicators was estimated using the Student’s t-test. Results. The analysis of the study results demonstrated that after using a combined method of strength development (1-6 classes), the experimental group boys showed a statistically significant improvement in results in the set of tests ( p < 0.05). After using a combined method of strength development, the 6th-8th grade boys had the largest increase in the results of strength and strength endurance of shoulder muscles, strength and strength endurance of abdominal muscles, strength and static strength endurance of leg muscles ( p < 0.05). After using a circuit training method (7-12 classes), the experimental group boys also showed a statistically significant improvement in results in the set of tests ( p < 0.05). The 6th-8th grade boys had the largest increase in the results of dynamic and static strength endurance of shoulder muscles, abdominal and back muscles, leg muscles (p < 0.05). According to the Eurofit motor fitness tests, after using the combined method of strength development (1-6 classes) and the circuit training method (7-12 classes) in a 4-week training cycle, the experimental group boys showed a statistically significant improvement in results in the set of tests (p < 0.05). During the experiment, the 6th-8th grade boys of the control group showed no statistically significant improvement in test results for most parameters (p > 0.05). A comparison between the levels of strength fitness of the control group boys and experimental group boys after the experiment showed that the experimental group boys had statistically significantly better results of strength and strength endurance of shoulder muscles, abdominal and back muscles, leg muscles (p < 0.05). Conclusions. After using the combined method of strength development (1-6 classes) and the circuit training method (7-12 classes) in a 4-week physical training cycle, the middle-school-aged boys showed positive dynamics of strength and strength endurance development of shoulder muscles, abdominal and back muscles, leg muscles. The dynamics of strength and static endurance of the local muscle group is strongly influenced by the combined method of strength development. The circuit training method is effective to develop dynamic and static strength endurance of the local muscle group. For overall development of strength and general endurance, it is effective to use a combination of the combined method of strength development and circuit training method in a 4-week physical training cycle.